Filter materials and filter components
By designing the connecting layer and protective functional layer in the filter material, combining ultrasonic composite and wire layer technology, the high resistance and catalyst peeling problems of the composite structure in the prior art are solved, and efficient filtration and long-life filtration effects are achieved.
Patent Information
- Application Number
- CN201910934057.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2019-09-26
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2039-09-26
AI Technical Summary
Existing filter materials have high filtration resistance and structural instability in the composite structure. The catalyst of chemical adsorbent gas pollutant is prone to fall off and the loss of function is caused by improper installation of different functional layers in the filtration system, resulting in low filtration efficiency and short life.
A composite filter material is designed, including a physical filter functional layer and a chemical filter functional layer. Through the optimized layout of the connecting layer and the protective functional layer, the tight connection and support between the functional layers are ensured, the resistance is reduced and the service life of the catalyst is extended. This material uses submicron-micron-scale petal-like particles formed by delta crystalline MnO2 as formaldehyde decomposition catalyst, and improves the stability of the filter material through the combination of ultrasonic composite and the wire layer.
It effectively reduces filtration resistance, extends the service life of the catalyst, improves filtration efficiency and material stability, reduces the space occupied by the filter material, and improves the purification effect.
Smart Images

Figure CN110614034B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of filter material preparation, in particular to filter materials and filter components. Background Art
[0002] Pollutants in the air are mainly divided into solid pollutants and gaseous pollutants. Solid pollutants in the air (such as PM10 and PM2.5) are generally removed by physical filtration (i.e., separation of specific objects by physical means); gaseous pollutants in the air (such as VOC, i.e., organic gaseous substances) are generally removed by chemical filtration (i.e., separation of specific objects by using the chemical properties of substances).
[0003] Fine particles in solid pollutants (such as PM2.5) are harmful to human health. In terms of removing fine particles by physical filtration, fiber filter materials with high filtration efficiency and good air permeability (such as glass fiber, PP fiber, PET fiber, expanded PTFE fiber, etc.) are particularly commonly used. However, during the use of such materials, bacteria are easily attached and breed on the fiber bundles, causing secondary pollution.
[0004] Formaldehyde is a substance that is most harmful to the human body among gaseous pollutants. In terms of removing formaldehyde by chemical filtration, the use of manganese dioxide in metal oxides as a formaldehyde decomposition catalyst has been considered to be a feasible method and has certain advantages in some aspects. At present, manganese dioxide used as a formaldehyde decomposition catalyst is limited to nano-scale manganese dioxide, so that it can have a sufficient specific surface area so that the formaldehyde decomposition catalyst can achieve an acceptable formaldehyde removal efficiency. The life of existing formaldehyde decomposition catalytic filtration devices is usually short. In addition to the life of the formaldehyde decomposition catalyst itself, one of the main reasons is that the formaldehyde decomposition catalyst falls off from the breathable support.
[0005] Since the air often contains different kinds of pollutants at the same time, in order to remove these pollutants, filter devices with different filtering objects are usually connected in series to form a filtering system. The filtering system can be composed of individual independent filtering devices or integrated with filtering devices. When the filtering system is integrated with filtering devices, the filtering materials of different filtering devices are either relatively independently installed in the same shell component or assembled as relatively independent components.
[0006] In the prior art, when filter materials of different filter devices are relatively independently installed in the same shell component, the filter materials are usually composited by directly overlapping or adhering them. There are gaps between the directly overlapping filter materials. On the one hand, the disturbance of the filter material by the gap during filtration will cause greater flow resistance of the filter material. On the other hand, the filter material may swing or collide under the action of the filter material, reducing the stability of the structure, thereby affecting the service life and use effect. When the composite is composited by adhesion, a viscose bonding surface or a sintering bonding surface is usually formed on the interface between the functional layers attached to each other. These bonding surfaces will cause a certain blocking effect on the flow of the filter material, which will increase the filtration resistance. Summary of the invention
[0007] The first object of the present invention is to provide a filter material, which solves the problem of high filtration resistance caused by improper compounding of filter materials in the prior art, optimizes the technical problem of the composite structure of different functional layers in the filter material, and solves the technical problem of loss of function caused by the detachment of the catalyst of chemical adsorption of gaseous pollutants. The second object of the present invention is to provide a filter assembly and a filter, also to solve the above technical problems. The third object of the present invention is to provide a method for preparing a filter material to obtain a composite filter material that does not affect the filtration resistance.
[0008] In order to achieve the first objective, a first filter material is provided. The filter material has different functional layers, wherein all functional layers include a physical filtration functional layer and a chemical filtration functional layer, wherein the physical filtration functional layer and the chemical filtration functional layer overlap each other in the filtration direction; the chemical filtration functional layer includes a chemical filtration layer for filtering at least one volatile organic compound; the physical filtration functional layer includes a first physical filtration layer for filtering solid particles in a to-be-filtered object; and the filter material further includes a connecting layer for connecting two adjacent functional layers.
[0009] Furthermore, the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; preferably, the formaldehyde decomposition catalyst is mainly composed of submicron-micron petal-shaped particles formed by delta crystal MnO2.
[0010] Furthermore, the first physical filter layer is a fiber filter layer or a metal filter layer; or the first physical filter layer is formed by overlapping a metal filter layer and a fiber filter layer, and a connecting layer is provided between the metal filter layer and the fiber filter layer.
[0011] Furthermore, the physical filtration functional layer also includes a second physical filtration layer for filtering at least one volatile organic compound, and the first physical filtration layer and the second physical filtration layer overlap front and back along the filtration direction; the second physical filtration layer includes activated carbon.
[0012] Furthermore, the second physical filtration layer is formed by stacking activated carbon powder, and the connecting layer between the physical filtration functional layer and the chemical filtration functional layer is arranged between the first physical filtration layer and the chemical filtration layer and encloses a stacking space for the activated carbon powder.
[0013] Furthermore, all functional layers include a protective functional layer, the chemical filtration functional layer and the protective functional layer overlap front and back along the filtration direction, the protective functional layer has a porous structure and the pore size is smaller than the particle size of the catalyst in the chemical filtration layer; preferably, the protective functional layer is PP fiber felt, PET fiber felt or electrostatic cotton.
[0014] Furthermore, the connecting layer is a rubber layer and / or an ultrasonic composite layer.
[0015] Furthermore, the rubber wire layer comprises multiple layers of rubber wire units distributed from top to bottom, and the deposition directions of two adjacent layers of rubber wire units are different; the rubber wire units are composed of rubber wires with a diameter of ≤0.1 mm arranged at a certain interval.
[0016] Furthermore, the ultrasonic composite layer is composed of one or more ultrasonic composite lines, and the ultrasonic composite lines are composed of composite nodes with a length of ≤3 mm and a width of ≤1 mm arranged at a spacing of 1 to 3 mm.
[0017] In order to achieve the first purpose, a second filter material is provided. The filter material has different functional layers, all of which include a chemical filtration functional layer and a protective functional layer, the chemical filtration functional layer and the protective functional layer overlap front and back along the filtration direction; the chemical filtration functional layer includes a chemical filtration layer for filtering at least one volatile organic compound; the protective functional layer has a porous structure and a pore size smaller than the particle size of the catalyst in the chemical filtration layer.
[0018] Furthermore, the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; preferably, the formaldehyde decomposition catalyst is mainly composed of submicron-micron petal-shaped particles formed by delta crystal MnO2.
[0019] Furthermore, the protective functional layer is PP fiber felt, PET fiber felt or electrostatic cotton.
[0020] Furthermore, all the functional layers also include a physical filtration functional layer, and the physical filtration functional layer overlaps with the chemical filtration functional layer front to back along the filtration direction; the physical filtration functional layer includes a first physical filtration layer for filtering solid particles in the filter material and / or a second physical filtration layer for filtering at least one volatile organic compound. When the physical filtration functional layer has both the first physical filtration layer and the second physical filtration layer, the first physical filtration layer and the second physical filtration layer overlap front to back along the filtration direction.
[0021] Furthermore, the first physical filter layer is a fiber filter layer or a metal filter layer; or the first physical filter layer is composed of a metal filter layer and a fiber filter layer arranged front and back along the filtering direction; and the second physical filter layer includes activated carbon.
[0022] Furthermore, the filter material also includes a connecting layer connecting two adjacent functional layers.
[0023] Furthermore, the connecting layer is a rubber layer and / or an ultrasonic composite layer.
[0024] Furthermore, the rubber wire layer comprises multiple layers of rubber wire units distributed from top to bottom, and the deposition directions of two adjacent layers of rubber wire units are different; the rubber wire units are composed of rubber wires with a diameter of ≤0.1 mm arranged at a certain interval.
[0025] Furthermore, the ultrasonic composite layer is composed of one or more ultrasonic composite lines, and the ultrasonic composite lines are composed of composite nodes with a length of ≤3 mm and a width of ≤1 mm arranged at a spacing of 1 to 3 mm.
[0026] Furthermore, symmetrically distributed connection layers are only provided locally between two adjacent functional layers.
[0027] In order to achieve the first objective, a third filter material is provided. The filter material has different functional layers, wherein all functional layers include a physical filtration functional layer and a chemical filtration functional layer, wherein the physical filtration functional layer and the chemical filtration functional layer overlap in the front and back direction of the filtration; the chemical filtration functional layer includes a chemical filtration layer for filtering at least one volatile organic compound; the physical filtration functional layer includes a second physical filtration layer for filtering at least one volatile organic compound; and the filter material further includes a connecting layer for connecting two adjacent functional layers.
[0028] Furthermore, the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; preferably, the formaldehyde decomposition catalyst is mainly composed of submicron-micron petal-shaped particles formed by delta crystal MnO2.
[0029] Furthermore, the physical filtration functional layer further comprises a first physical filtration layer for filtering solid particles in the object to be filtered, and the first physical filtration layer and the second physical filtration layer overlap front and back along the filtering direction.
[0030] Furthermore, the second physical filtration layer is formed by stacking activated carbon powder, and the connecting layer between the physical filtration functional layer and the chemical filtration functional layer is arranged between the first physical filtration layer and the chemical filtration layer and encloses a stacking space for the activated carbon powder.
[0031] Furthermore, the first physical filter layer is a fiber filter layer or a metal filter layer; or the first physical filter layer is composed of a metal filter layer and a fiber filter layer arranged front and back along the filtering direction, and a connecting layer is provided between the metal filter layer and the fiber filter layer.
[0032] Furthermore, all functional layers include a protective functional layer, the chemical filtration functional layer and the protective functional layer overlap front and back along the filtration direction, the protective functional layer has a porous structure and the pore size is smaller than the particle size of the catalyst in the chemical filtration layer; preferably, the protective functional layer is PP fiber felt, PET fiber felt or electrostatic cotton.
[0033] Furthermore, the connecting layer is a rubber layer and / or an ultrasonic composite layer.
[0034] Furthermore, the rubber wire layer comprises multiple layers of rubber wire units distributed from top to bottom, and the deposition directions of two adjacent layers of rubber wire units are different; the rubber wire units are composed of rubber wires with a diameter of ≤0.1 mm arranged at a certain interval.
[0035] Furthermore, the ultrasonic composite layer is composed of one or more ultrasonic composite lines, and the ultrasonic composite lines are composed of composite nodes with a length of ≤3 mm and a width of ≤1 mm arranged at a spacing of 1 to 3 mm.
[0036] The above three filter materials have the following advantages: (1) By setting a connecting layer, the problem of increased resistance to the filtered material due to disturbance of the filtered material by a large gap can be avoided, making the filtering process smoother; it has been verified that the resistance to the filtered material can be reduced by at least 30%; (2) By setting a connecting layer, multiple functional layers can be combined into one, avoiding damage caused by shaking and mutual collision of the functional layers; (3) By setting a protective functional layer, the catalyst falling off from the chemical filtration layer can be intercepted, thereby extending the service life of the catalyst; it has been verified that the service life of the chemical filtration layer can be extended by 30%; (4) The protective functional layer can also The functional layer located in front of the protective functional layer in the filter material is supported in the direction opposite to the filtering direction; (5) There are two functional layers that filter at least one volatile organic compound, specifically a second physical filtration layer and a chemical filtration layer, which not only makes the purification more thorough, but also places the second physical filtration layer in front of the chemical filtration layer, which can reduce the probability of catalyst poisoning in the chemical filtration layer and further extend the service life of the catalyst; (6) Since the functional layers are connected as a whole through the connecting layer, the functional layers can support each other, thereby reducing the use of positioning components and / or supporting components when installing the filter material, which helps to reduce the space occupied by the filter material.
[0037] The adhesive layer is composed of ultra-fine hot-melt adhesive threads distributed in a disordered manner or at a certain interval. Therefore, unlike the densely distributed adhesive layer, the adhesive layer of the present application has both connection function and air permeability. It has been verified that when the diameter of the adhesive thread is ≤ 0.1 mm, the effect on the air permeability of the filter material can be negligible.
[0038] The principle of ultrasonic compounding is to use high-frequency vibration waves to transmit to two or more material surfaces, and under pressure, the material surfaces rub against each other to form a fusion between molecular layers. The ultrasonic compound line is composed of very small compound nodes, so it has little effect on the air permeability of the filter material; when the ultrasonic compound line is composed of compound nodes with a length of ≤3mm and a width of ≤1mm arranged at a spacing of 1 to 3mm, the effect on the air permeability of the filter material can be so small that it can be ignored.
[0039] Compared with the ultrasonic composite layer, the rubber thread layer can be obtained more quickly, but the connection method of the rubber thread layer is physical connection, while the fusion layer connects the two functional layers into one through chemical bonds, which has better bonding force and helps to improve the stability of the filter material during use.
[0040] In order to further reduce the influence of the connecting layer on the air permeability of the filter material, preferably, a symmetrically distributed connecting layer is only set locally between two adjacent functional layers. When ultrasonic compounding is adopted, even if it is only set locally, since the ultrasonic compound layer is formed under pressure, the gap between the contact surfaces of the adjacent functional layers where the ultrasonic compound layer is not set can also be ignored. When the rubber wire layer is adopted, the thickness of the rubber wire layer can be controlled to be less than 50μm. Therefore, the gap between the functional layers where the rubber wire layer is not set is very small, and the disturbance of the filter material to be filtered by the gap can also be ignored. And because the connecting layer is evenly distributed, the filter material is more evenly stressed during use, which can further reduce the shaking and mutual collision of the functional layers of the filter material. At the same time, because the gap is very small, the collision force between the functional layers is small, and the functional layer is not easily damaged. When the connecting layer is set locally, in order to ensure the connection effect, it is preferred that the width of the connecting layer is 3 to 6cm, and the length is ≥1 / 3 times the length of the filter material (the connecting layer is set along the length direction of the filter material) or the width (the connecting layer is set along the width direction of the filter material).
[0041] Among the above three types of filter materials, it is preferred that the first physical filter layer is composed of a metal filter layer and a fiber filter layer that overlap front and back along the filtering direction; such an arrangement has the following effects: (1) Since most metal filter layers are conductive, the metal filter layer can also serve as a conductive layer. In this way, when the metal filter layer is charged by an external power supply, the metal filter layer can repel or adsorb charged particles in the filter material, thereby improving the filtering efficiency of the filter material; at the same time, since most fiber filter layers have insulating properties, when the metal filter layer also serves as a conductive layer, the fiber filter layer can serve as an insulating layer for the conductive layer, so as to insulate the metal filter layer from the shell and / or other components (such as other functional layers of the filter material) on which the filter material is installed. (2) When the metal filter layer also serves as a conductive layer and the fiber filter layer serves as an insulating layer for the conductive layer, since the fiber filter layer acts as an insulator between the metal filter layer and the chemical filter functional layer, it is possible to avoid the adverse effects of the metal filter layer being charged on the catalyst in the chemical filter functional layer, such as avoiding the metal filter layer being charged on the electronic structure of the catalyst surface and reducing the catalytic activity. In addition, regardless of whether the metal filter layer is connected to an external power source, its surface may carry a certain charge. If the fiber filter layer is set as a fiber filter layer with electrical insulation properties, it is possible to avoid the adverse effects of the surface charge of the metal filter layer on the catalyst. (3) The filtered material is first filtered once by the metal filter layer and then filtered twice by the fiber filter layer. Therefore, the number of bacteria and other microorganisms entering the fiber filter layer is reduced, thereby reducing the adhesion and growth of bacteria in the fiber filter layer. The metal filter layer has relatively good antibacterial properties and bacteria are not easy to reproduce. In this way, the problem of bacterial growth on the filter material as a whole can be improved to a certain extent.
[0042] When the filter material has both a metal filter layer and a fiber filter layer, the filtering method has the following steps: controlling the charging mode of the metal filter layer according to the pollutant components in the air to be filtered: when the solid particle content in the air rises to a set threshold and / or the volatile organic compound content drops to a set threshold, the metal filter layer is charged; when the solid particle content in the air drops to an established threshold and / or the volatile organic compound content rises to an established threshold, the metal filter layer is uncharged.
[0043] The metal filter layer is mainly made of metal (including alloy). The metal filter layer is preferably a metal filter layer mainly composed of powder sintered metal porous material; more preferably a flexible metal film with a thickness of ≤200μm and foldable. The thickness of the flexible metal film is ≤200μm, so it is easier to achieve higher air permeability. Since the flexible metal film itself is foldable, it does not affect the bending or folding of the filter material shape. The flexible metal film can be a porous film prepared by the method provided in the Chinese patent document CN104874798A, or a flexible metal film prepared by other methods. This application particularly recommends the use of a product with the commercial name of "paper-type membrane" manufactured by the applicant of this application based on the content of the above-mentioned CN104874798A patent document. The paper-type membrane is a flexible metal film containing a mesh skeleton and a powder sintered metal porous material filled in the skeleton mesh, and its thickness can reach ≤200μm and it is foldable.
[0044] The average pore size of the paper-type membrane (or other metal filter layer) is generally set within the range of 5 to 200 μm. The upper limit of the range can also be set to 190 μm, 180 μm, 170 μm, 160 μm, 150 μm, 140 μm, 130 μm, 120 μm, 110 μm or 100 μm as required; the lower limit of the range can also be set to 10 μm, 20 μm, 30 μm, 40 μm, 50 μm, 60 μm, 70 μm, 80 μm, 90 μm or 100 μm as required. In order to achieve a better balance between air permeability and filtration efficiency of the metal filter layer, the average pore size of the metal filter layer can generally be 10 to 150 μm, further 10 to 120 μm, further 10 to 100 μm, and further 10 to 80 μm. When the filter material includes a chemical filtration functional layer, the average pore size of the metal filter layer can be appropriately increased, considering that the chemical filtration functional layer will have a certain impact on the overall air permeability of the filter material. For example, when the filter material is composed of a metal filter layer, a fiber filter layer, a formaldehyde decomposition catalytic felt and a protective functional layer, the average pore size of the metal filter layer is set between 40 and 90 μm, such as about 42 μm, about 55 μm, 79 μm and 85 μm, etc. At this time, the use effect of these metal filter layers is satisfactory.
[0045] The above term "average pore size" is a commonly used parameter for characterizing porous materials and can be measured by the bubble method. The relevant technology involved in the patent application document with publication number CN104266952A applied by the applicant of this application can be used to measure the average pore size of the metal filter layer. The above term "filtration efficiency" refers to the ratio of the amount of solid particles intercepted by the filter material to the amount of solid particles contained in the gas to be filtered under test conditions.
[0046] The metal filter layer may contain some metal substances with bactericidal function, such as copper, silver, etc. Therefore, the powder sintered metal porous material of the metal filter layer is preferably composed of a copper-nickel alloy formed by powder sintering. Such a metal filter layer can meet the "flexibility" requirement and has a certain bactericidal function.
[0047] The fiber filter layer is mainly made of inorganic non-metallic fibers (such as glass fibers), organic fibers (such as PP fibers) or their composite materials. Usually, the fiber filter layer is mainly composed of at least one fiber filter material selected from glass fibers, PP fibers, PET fibers, and expanded PTFE fibers. Generally speaking, the filtration efficiency of the fiber filter layer for solid particulate matter is higher than that of the metal filter layer for solid particulate matter. The fiber filter layer is preferably a fiber filter layer mainly composed of ultrafine fiber filter material, so that the fiber filter layer can have better filtration efficiency and air permeability. The "ultrafine fiber filter material" should be understood as: a fiber filter material whose diameter enables the prepared fiber filter layer to remove more than 98% of dust with a particle size of ≥2.5μm in the gas to be filtered. The above-mentioned glass fibers, PP fibers, PET fibers, and expanded PTFE fibers can all be ultrafine fiber filter materials. When the fiber filter layer is mainly composed of ultrafine fiber filter material, it is more appropriate to select the average pore size of the metal filter layer to be 10-100 μm, and it is particularly appropriate to select the average pore size of the metal filter layer to be 20-80 μm.
[0048] According to experience, the filtration accuracy of the porous filter medium is approximately equal to 1 / 10 of its average pore size. For example, when the average pore size of the metal filter layer is 80μm, its filtration accuracy is about 8μm. In addition, during filtration, a filter cake will gradually form on the metal filter layer, thereby further increasing the filtration accuracy, that is, the filtration accuracy is less than 8μm. In other words, when the average pore size of the metal filter layer is 80μm, it can intercept solid particles (dust) with a particle size of ≤8μm during filtration. That is, when the average pore size of the metal filter layer is selected to be 10-100μm, the metal filter layer can intercept a large part of solid particles with larger particle sizes such as PM10, a large part of mold spores (the particle size distribution range in the air is mainly 1-100μm) and a part of bacteria (the particle size distribution range in the air is mainly 0.5-10μm). In this way, the adhesion and growth of mold and bacteria on the fiber filter layer can be effectively reduced. However, when the average pore size of the metal filter layer is closer to the lower limit of 10-100 μm, the air permeability of the entire filter material, especially the other functional layers in addition to the metal filter layer and the fiber filter layer, is lower. Therefore, it is best to select the average pore size of the metal filter layer and other related technical parameters according to the overall filtering performance index of the filter material.
[0049] In order to achieve the second objective, according to one aspect of the present invention, a filter assembly is provided, which includes a filter portion using one of the three filter materials mentioned above.
[0050] The filter assembly is a specific method designed to configure the filter material as an independent module that can be detached from a parent device such as a filter when the above-mentioned filter material is used, so as to facilitate the independent manufacture, sale, installation and replacement of the filter assembly. The filter assembly also includes a positioning part and a sealing part, the positioning part includes a positioning frame arranged around the filter material so as to confine the filter material inside and open both sides of the filter material to the outside, and the sealing part includes a sealing material arranged between the filter material and the positioning part to prevent the filtered material from penetrating the inner boundary area of the positioning frame without passing through the filter material.
[0051] Furthermore, the positioning portion is provided with a conductive component for conductively connecting with the metal filter layer in the filter material; the metal filter layer is insulated and installed in the filter assembly and can be charged by the conduction of the conductive component. Thus, the metal filter layer can be insulated and installed in the filter assembly and can be charged by the conduction of the conductive component. The conductive component can be any conductor, which is located on the positioning portion and is preferably arranged in a manner that can automatically contact the electrical connection terminal on the parent device such as the filter after the filter assembly is installed in the parent device such as the filter.
[0052] Furthermore, the sealing material of the sealing part can be a sealant directly bonded between the periphery of the filter material and the positioning frame, or can further include a sealing plate located at the edge of the filter material, wherein the inner side of the sealing plate is bonded to the surface where the corresponding filter material edge is located by the sealant, and the outer side is bonded to the inner side of the corresponding positioning frame by the sealant. Thus, the sealing plate can be bonded to the filter material first, and then the filter material bonded with the sealing plate can be sealed and installed in the positioning frame, so the sealing plate can facilitate the sealing installation of the filter material in the positioning frame. However, the provision of the sealing plate will increase the manufacturing cost of the filter assembly and occupy some space.
[0053] Further, the filter material has a rectangular pleated structure, one pair of opposite sides of the filter material is a pleated wave-shaped side, and the other pair of opposite sides is a straight line side; the positioning frame is a rectangular positioning frame matching the filter material, and the surface of the filter material where the straight line side is located is directly bonded to the corresponding inner side of the positioning frame through a sealant, and the pleated wave-shaped side is bonded to the corresponding inner side of the positioning frame through at least one sealing plate. The filter material with a pleated structure can greatly increase the filtration area of the filter material compared to the filter material with a smooth surface, thereby improving the filtration efficiency. At this time, the surface of the filter material where the straight line side is located is directly bonded to the corresponding inner side of the positioning frame through a sealant, and the pleated wave-shaped side is bonded to the corresponding inner side of the positioning frame through at least one sealing plate. In this way, not only the purpose of facilitating the sealing installation of the filter material in the positioning frame and effectively sealing the pleated wave-shaped side can be achieved through the sealing plate, but also the number of sealing plates used is saved, and since the surface of the filter material where the straight line side is located and the corresponding inner side of the positioning frame are bonded face to face, a good sealing effect can be achieved. When the filter material has a pleated structure, the protective functional layer not only intercepts the catalyst falling off from the chemical filtration layer and supports the functional layer in the filter material located before the protective functional layer in the direction opposite to the filtration direction, but also has the function of positioning and conforming the pleat waves of the pleated structure, which can prevent the deformation of the pleat waves to a certain extent and avoid inconsistent gaps between the pleat waves.
[0054] Further, the positioning frame includes: a side positioning frame, a sealing material is arranged between the side positioning frame and the filter material; an upper positioning frame, the upper positioning frame is arranged at the upper end of the side positioning frame and extends along the top edge of the side positioning frame; and a lower positioning frame, the lower positioning frame is arranged at the lower end of the side positioning frame and extends along the bottom edge of the side positioning frame. Thus, the filter material is better fixed and sealed. Preferably, the upper positioning frame is preferably connected to the side positioning frame in a split manner, so that the upper positioning frame can be installed on the side positioning frame after the filter material is loaded into the positioning frame. Further preferably, the bottom surface of the upper positioning frame is designed as a step surface adapted to the upper end of the side positioning frame, and the sealant between the upper positioning frame and the side positioning frame is basically covered with two parallel planes on the step surface, so that it can facilitate the installation and positioning of the upper positioning frame and ensure the sealing effect of the upper positioning frame on the filter material. The upper positioning frame and the lower positioning frame can limit the filter material and better restrict it in the side positioning frame.
[0055] Furthermore, the positioning portion of the filter assembly includes a pleated conformal component disposed on the side of the filter material, and the pleated conformal component may include supports disposed between multiple pairs of adjacent pleated waves of the filter material at intervals. Although the filter material with a pleated structure can greatly increase the filtration area of the filter material compared to the filter material with a smooth surface, thereby improving the filtration efficiency, the pleated waves of the pleated structure may be deformed during use, resulting in inconsistent gaps between the pleated waves, and finally resulting in uneven filtration flux distributed on the filter material. The deformation of the pleated waves is prevented by supports disposed between multiple pairs of adjacent pleated waves of the filter material on the pleated conformal component, thereby ensuring the uniformity of the filtration flux distributed on the filter material. Preferably, the supports are composed of positioning glue that is respectively filled between the multiple pairs of adjacent pleated waves and solidified. The supports formed in this way are low in cost, easy to make, and can be bonded to the pleated waves without falling off easily. Further preferably, the positioning glue is only filled between the peaks of the corresponding adjacent pleat waves, thereby reducing the laying area of the positioning glue on the filter material and reducing the influence of the positioning glue on the filtration efficiency; the depth of the positioning glue filled in the gap between the peaks of the corresponding adjacent pleat waves is preferably not more than 1.5cm, 1.2cm, 1cm, 0.8cm or 0.5cm. The depth of the positioning glue filled in the gap between the peaks of the corresponding adjacent pleat waves is related to factors such as the characteristics of the filter material. For example, when the filter material is relatively soft, it is not easy for the positioning glue to be only filled between the peaks of the corresponding adjacent pleat waves, because the positioning glue is difficult to play an effective supporting role for the pleat waves. When a metal filter layer is provided, the metal filter layer has a high deformation resistance, and the metal filter layer is preferably a metal filter layer mainly composed of powder sintered metal porous material and has an ideal surface roughness so that the positioning glue is arranged on the surface of the metal filter layer to achieve the effect that the positioning glue is only filled between the peaks of the corresponding adjacent pleat waves. The positioning glue may also form a continuous positioning glue thread on the side of the filter material. In this case, the pleat shape-keeping component may include at least two positioning glue threads that do not overlap with each other and are arranged on the side of the filter material.
[0056] In order to achieve the second objective, according to one aspect of the present invention, a filter is provided, which includes an air inlet, an air outlet, and an air duct between the air inlet and the air outlet, wherein one of the three filter assemblies is installed on the air duct, and the windward side of the filter assembly is connected to the air inlet, and the air outlet side is connected to the air outlet.
[0057] Furthermore, the filter is also used by an air conditioner with air filtering function. Due to the special structure of the filter material, the filter assembly is thinner, and the filter assembly can be directly installed in an existing household air conditioner.
[0058] In order to achieve the third objective, a method for preparing a filter material is provided. The filter material comprises a physical filter function layer and a chemical filter function layer overlapping in a filtering direction, wherein the physical filter function layer comprises a first physical filter layer overlapping in a filtering direction for filtering solid particles in a to-be-filtered object and a second physical filter layer for filtering at least one volatile organic compound, wherein the second physical filter layer comprises activated carbon; the method for preparing the filter material comprises the following steps:
[0059] (1) Sprinkling activated carbon powder on the surface of the chemical filtration functional layer or the first physical filtration layer to form a second physical filtration layer;
[0060] (2) A connecting layer is formed by spraying glue and / or ultrasonic compounding to connect the first physical filtration layer and the chemical filtration functional layer and is located around the second physical filtration layer, thereby obtaining a filter material.
[0061] When the filter material has a pleated structure, the method for preparing the filter material should also include step (3) of integrally deforming the blank of all functional layers of the stacked filter material into a filter material of a specific shape.
[0062] Furthermore, the particle size of the activated carbon powder is 0.01 to 5 mm, preferably 0.03 to 1 mm, and further preferably 0.05 to 0.3 mm. The smaller the particle size of the activated carbon particles, the higher the packing density and the larger the specific surface area, but the airflow resistance will increase. Therefore, considering the airflow resistance and adsorption efficiency, the most preferred particle size of the activated carbon powder is 0.05 to 0.3 mm.
[0063] Furthermore, the method further includes scraping and compacting the activated carbon powder accumulation layer. In order to control the surface deformation of the first physical filtration layer and the chemical filtration functional layer caused by the uneven surface of the second physical filtration layer, the activated carbon powder accumulation layer is scraped and compacted, so that the surface of the second physical filtration layer is flat, the second physical filtration layer is in closer contact with the first physical filtration layer and the chemical filtration functional layer, and the activated carbon powder does not slide during use, and can always maintain a flat surface.
[0064] Furthermore, the first physical filter layer is a fiber filter layer or a metal filter layer; or the first physical filter layer is composed of a metal filter layer and a fiber filter layer overlapping front and back along the filtering direction, and a connecting layer formed by spraying and / or ultrasonic compounding is provided between the metal filter layer and the fiber filter layer.
[0065] Furthermore, all functional layers include a protective functional layer, the chemical filtration functional layer and the protective functional layer overlap front and back along the filtration direction, and a connecting layer formed by spraying and / or ultrasonic compounding is provided between the chemical filtration functional layer and the protective functional layer, and the protective functional layer has a porous structure and a pore size smaller than the particle size of the catalyst in the chemical filtration functional layer.
[0066] Furthermore, it also includes using a lap strip whose thickness matches the thickness of the second physical filter layer, the lap strip is located between the first physical filter layer and the chemical filter functional layer and encloses the placement space of the activated carbon powder, and the upper and lower surfaces of the lap strip are respectively connected to the first physical filter layer and the chemical filter functional layer by spraying glue and / or ultrasonic composite connection; preferably, the lap strip has a porous structure. Since the activated carbon powder accumulation layer has a certain thickness, if the first physical filter layer and the chemical filter functional layer are connected by ultrasonic composite connection, if the accumulation layer is thick, the surface of the first physical filter layer and the chemical filter functional layer will be deformed to a certain extent. By setting the lap strip, the supporting effect of the lap strip can reduce the surface deformation caused by the partition of the second physical filter layer when the first physical filter layer and the chemical filter functional layer are connected. When the lap strip is used, the activated carbon can be sprinkled after the lap strip is installed on the surface of the chemical filter functional layer or the first physical filter layer, which is more convenient to operate and can also facilitate the scraping and compacting of the activated carbon powder accumulation layer.
[0067] Furthermore, it also includes using a mold to prevent the activated carbon powder from falling into the connection layer, and the mold has a through hole that matches the size of the second physical filter layer. In order to place the activated carbon more efficiently and prevent the activated carbon from falling into the connection between the first physical filter layer and the chemical filter layer, a mold can be used to assist, and the mold has a through hole whose shape and thickness match the second physical filter layer, thereby directly sprinkling the activated carbon into the through hole. When the mold is used, in addition to preventing the activated carbon from falling into the connection between the first physical filter layer and the chemical filter layer, it is also convenient to scrape and compact the accumulated layer of the activated carbon powder.
[0068] Furthermore, each butting surface has multiple connection layers which are symmetrically distributed.
[0069] Furthermore, the connecting layer formed by spraying glue is a rubber thread layer, which includes multiple layers of rubber thread units distributed from top to bottom, and the deposition directions of two adjacent layers of rubber thread units are different; the rubber thread units are composed of rubber threads with a diameter of ≤0.1mm arranged at a certain interval; the width of the rubber thread layer is 3 to 6cm.
[0070] Furthermore, the connection layer formed by ultrasonic compounding is an ultrasonic compound layer, which is composed of one or more ultrasonic compound lines, and the ultrasonic compound lines are composed of compound nodes with a length of ≤3mm and a width of ≤1mm arranged at a spacing of 1 to 3mm.
[0071] In the above preparation method, in order to control the surface deformation amount caused by the partition of the second physical filtration layer when the first physical filtration layer is connected to the chemical filtration functional layer, if the lap strip is not used, a rubber wire layer matching the thickness of the second physical filtration layer can also be used to connect the chemical filtration layer and the first physical filtration layer. The thickness of the rubber wire layer can be controlled by controlling the number of rubber wire units. In order to fully reduce the surface deformation of the first physical filtration layer and the chemical filtration layer, it is preferred that the thickness of the rubber wire layer is equal to the thickness of the second physical filtration layer. And between other functional layers, the thickness of the rubber wire layer should be thin enough. Of course, the activated carbon can also be placed in a rectangular frame with openings, and then the upper and lower surfaces of the rectangular frame are respectively connected to the chemical filtration layer and the first physical filtration layer, but this is bound to increase the volume and weight of the filter material to a great extent.
[0072] The technical solutions of the formaldehyde decomposition catalyst, formaldehyde catalytic decomposition felt and their manufacturing methods involved in the above technical solution and which are very suitable are as follows:
[0073] The formaldehyde decomposition catalyst is mainly composed of submicron-micron petal-shaped particles formed by delta-crystalline MnO2. The "submicron-micron petal-shaped particles" refer to a combination of submicron petal-shaped particles with a diameter in the range of 0.1 to 1 μm and micron petal-shaped particles with a diameter in the range of 1 to 10 μm. Generally, the diameter distribution range of submicron-micron petal-shaped particles is ≥ 0.5 μm. That is, the diameter of the micron-sized petal-shaped particles with the largest diameter among these submicron-micron petal-shaped particles is at least 0.5 μm larger than the diameter of the submicron-sized petal-shaped particles with the smallest diameter.
[0074] Furthermore, the diameter of the submicron-micron petal-shaped particles is mainly distributed between 0.1 and 5 μm, more specifically, mainly distributed between 0.3 and 5 μm. Furthermore, the diameter of the submicron-micron petal-shaped particles is mainly distributed between 0.5 and 5 μm; further, the diameter of the submicron-micron petal-shaped particles is mainly distributed between 0.5 and 3 μm.
[0075] Furthermore, the water washing liquid of the submicron-micron petal-shaped particles is alkaline.
[0076] The formaldehyde catalytic decomposition felt comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support, wherein the formaldehyde decomposition catalyst is any one of the above-mentioned formaldehyde decomposition catalysts.
[0077] Furthermore, the formaldehyde decomposition catalyst is distributed on the outside of the material constituting the breathable support and is mainly filled in the pores between the materials constituting the breathable support.
[0078] Furthermore, it comprises an adhesive distributed on the formaldehyde decomposition catalyst; the adhesive is preferably, but not limited to, an acrylic adhesive or a polyurethane adhesive.
[0079] Furthermore, if the relative attachment amount of the formaldehyde decomposition catalyst on the breathable support is obtained by dividing the weight of the formaldehyde decomposition catalyst by the area of the windward surface of the breathable support, the relative attachment amount is 40 g / m 2 above.
[0080] Furthermore, the air permeability of ... 3 / m 2 ·h breathable fiber felt, preferably with an air permeability of ≥5500m at a pressure difference of 100Pa 3 / m 2 h of air-permeable fiber felt; and the relative attachment amount is 40 to 120 g / m 2 , preferably 50 to 70 g / m 2 .
[0081] Furthermore, the breathable support is made of PP fiber felt or PET fiber felt.
[0082] Furthermore, the breathable support material adopts a foam-like porous support body or a support net; when the breathable support material adopts a support net, the support net can be any one of a woven net, a punched net, and a diagonal net.
[0083] The above-mentioned formaldehyde decomposition catalyst and the formaldehyde catalytic decomposition felt using the formaldehyde decomposition catalyst involve MnO2 particles with specific crystal form, micromorphology, diameter size and diameter distribution. The MnO2 particles are obtained based on a large-scale production process developed by the applicant. The process not only greatly improves the production efficiency of the formaldehyde decomposition catalyst, but also the obtained product, i.e. the above-mentioned formaldehyde decomposition catalyst, has a formaldehyde removal effect that exceeds expectations and has an ideal formaldehyde removal efficiency compared to other existing formaldehyde decomposition catalysts.
[0084] As for the above-mentioned formaldehyde catalytic decomposition felt, by extruding and dispersing the formaldehyde decomposition catalyst in the pores between the materials constituting the breathable support, the technical problem of the formaldehyde decomposition catalyst being difficult to evenly distribute on the breathable support is well solved, which helps to further improve the formaldehyde removal effect of the formaldehyde catalytic decomposition felt.
[0085] When the formaldehyde catalytic decomposition felt is applied to the above-mentioned filter materials with different functional layers, the formaldehyde decomposition catalyst in the formaldehyde catalytic decomposition felt can be effectively prevented from being lost and poisoned along with the filtered material, thereby extending the life of the formaldehyde catalytic decomposition felt.
[0086] The method for preparing a formaldehyde decomposition catalyst comprises: using potassium permanganate, manganese sulfate and water as raw materials for mixed reaction to obtain the formaldehyde decomposition catalyst, and specifically comprising:
[0087] A. Potassium permanganate is prepared into a 60-110 g / L potassium permanganate solution and placed in the first titration tank, and manganese sulfate is prepared into a 70-120 g / L manganese sulfate solution and placed in the second titration tank. The molar ratio between potassium permanganate in the first titration tank and manganese sulfate in the second titration tank is 3:3 to 4:3. If the volume of the potassium permanganate solution in the first titration tank or the volume of the manganese sulfate solution in the second titration tank is set as the reference volume, the reference volume shall not be less than 50 L;
[0088] B. respectively drop the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank into the bottom water pre-stored in the mixing reactor with a volume more than twice the reference volume, drop the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank within 10 to 45 minutes, and then fully stir the mixed solution at 70 to 90° C. until the reaction is completed;
[0089] C. The formaldehyde decomposition catalyst is obtained by solid-liquid separation from the mixed liquid after the reaction is completed.
[0090] The invention discloses a method for manufacturing a formaldehyde decomposition catalyst. The method comprises performing alkali washing on a target object to obtain the alkali-washed formaldehyde decomposition catalyst. The target object is: 1) a formaldehyde decomposition catalyst obtained by mixing potassium permanganate, manganese sulfate and water as raw materials; 2) a precipitate obtained after step B in the method for manufacturing the formaldehyde decomposition catalyst; or 3) a formaldehyde decomposition catalyst obtained after step C in the method for manufacturing the formaldehyde decomposition catalyst.
[0091] The inventors have found that a formaldehyde decomposition catalyst prepared using potassium permanganate, manganese sulfate and water as raw materials has a detectable odor, and that the odor of the formaldehyde decomposition catalyst can be removed by alkaline washing, thereby improving the comfort of using the formaldehyde decomposition catalyst.
[0092] The manufacturing method of formaldehyde catalytic decomposition felt comprises: providing a breathable support; providing a slurry containing a formaldehyde decomposition catalyst; extruding and dispersing the slurry on the breathable support, and obtaining the formaldehyde catalytic decomposition felt after the slurry is dried; wherein the formaldehyde decomposition catalyst is: 1) any one of the above-mentioned formaldehyde decomposition catalysts; 2) a formaldehyde decomposition catalyst obtained by the manufacturing method of any one of the above-mentioned formaldehyde decomposition catalysts; or 3) a formaldehyde decomposition catalyst mainly composed of submicron-micron petal-shaped particles formed by delta-crystalline MnO2.
[0093] Furthermore, the slurry is attached to the breathable support through a slurry drawing process, and the extrusion dispersion process exists in the slurry drawing process.
[0094] The present invention is further described below in conjunction with the accompanying drawings and specific embodiments. Additional aspects and advantages of the present invention will be partially given in the following description, partially become apparent from the following description, or be learned through the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0095] The drawings constituting a part of the present invention are used to assist in understanding the present invention. The contents provided in the drawings and their related descriptions in the present invention can be used to explain the present invention, but do not constitute improper limitations on the present invention. In the drawings:
[0096] Figure 1 This is a schematic diagram of the structure of the filter material of Example 1 of the present invention.
[0097] Figure 2 This is a schematic diagram of the structure of the filter material of Example 2 of the present invention.
[0098] Figure 3 This is a schematic diagram of the structure of the filter material of Example 3 of the present invention.
[0099] Figure 4 This is a schematic structural diagram of the rubber wire layer of the filter material of Example 3 of the present invention.
[0100] Figure 5 This is a schematic diagram of the structure of the mold in the filter material preparation method of Example 3 of the present invention.
[0101] Figure 6 This is a schematic diagram of the structure of the filter material of Example 4 of the present invention.
[0102] Figure 7 This is a schematic diagram of the structure of the filter material of Example 5 of the present invention.
[0103] Figure 8 This is a schematic diagram of the structure of the filter material of Example 6 of the present invention.
[0104] Fig. 9Schematic diagram of the structure of the filter material of comparative example 1 of the present invention.
[0105] Fig.10 Schematic diagram of the structure of the filter material of comparative example 2 of the present invention.
[0106] Fig.11 It is a schematic diagram of the structure of the filter material with a pleated structure in the present invention.
[0107] Fig.12 It is a schematic diagram of the positioning glue filled and solidified between multiple pairs of adjacent pleat waves of the filter material in the present invention.
[0108] Fig.13 It is a schematic diagram of the structure of the filter assembly before the filter material is placed in the positioning frame in the present invention.
[0109] Fig.14 It is a schematic diagram of the structure of the filter assembly of the present invention.
[0110] Fig.15 It is a schematic diagram of the structure of the filter of the present invention.
[0111] Fig.16 This is a scanning electron microscope image of a formaldehyde decomposition catalyst of the invention involved in this application specification, wherein Figures (a)-(d) are photographs of the field of view selected on the slide without tendency during microscopic observation.
[0112] Fig.17 for Fig.16 X-ray diffraction (XRD) pattern of the formaldehyde decomposition catalyst shown.
[0113] Fig.18 This is a scanning electron microscope image of a formaldehyde catalytic decomposition felt of the invention involved in this application specification, wherein Figures (a)-(d) are photographs of the field of view selected on the slide without tendency during microscopic observation.
[0114] Fig.19 The scanning electron microscope images of the formaldehyde decomposition catalyst of Comparative Example 1 are shown, wherein Figures (a) and (b) are photographs of the field of view selected on the slide without tendency during microscopic observation.
[0115] Fig. 20 This is a graph showing the change in formaldehyde concentration over time when the formaldehyde decomposition catalyst of Example A1 is used to conduct a formaldehyde removal performance test.
[0116] Fig.21 This is a graph showing the change in formaldehyde concentration over time when the formaldehyde decomposition catalyst of Example A5 is used to conduct a formaldehyde removal performance test.
[0117] Fig. 22 This is a graph showing the change in formaldehyde concentration over time when the formaldehyde decomposition catalyst of Comparative Example 1 is used to conduct a formaldehyde removal performance test.
[0118] Fig.23 This is a scanning electron microscope image of a formaldehyde decomposition catalytic felt in the invention involved in this application specification.
[0119] Fig.24 This is a test chart of the comprehensive performance of the formaldehyde catalytic decomposition felt of Examples B1-B5.
[0120] Fig.25 This is a comparison chart of the distribution uniformity of the formaldehyde decomposition catalyst of the formaldehyde catalytic decomposition felt of Example B2 and Example B6.
[0121] The parts in the above drawings are marked as:
[0122] 120: chemical filtration functional layer;
[0123] 130: protection function layer;
[0124] 111: metal filter layer;
[0125] 112: fiber filter layer;
[0126] 113: second physical filter layer;
[0127] 410: Ultrasonic composite layer;
[0128] 411: Ultrasonic composite line;
[0129] 412: composite node;
[0130] 510: rubber layer;
[0131] 511: Rubber wire unit;
[0132] 512: Rubber wire;
[0133] 610: Overlap strip. DETAILED DESCRIPTION
[0134] The present invention is described clearly and completely below in conjunction with the accompanying drawings. A person skilled in the art will be able to implement the present invention based on these descriptions. Before describing the present invention in conjunction with the accompanying drawings, it should be particularly noted that:
[0135] The technical solutions and technical features provided in each part of the present invention, including the following description, may be combined with each other if there is no conflict.
[0136] In addition, the embodiments of the present invention involved in the following description are generally only a part of the embodiments of the present invention, rather than all the embodiments. Therefore, based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work should fall within the scope of protection of the present invention.
[0137] About the terms and units in the present invention: The terms "include", "have" and any variations thereof in the description and claims of the present invention and related parts are intended to cover non-exclusive inclusions.
[0138] Example 1
[0139] like Figure 1 As shown, the filter material of this embodiment has different functional layers, and all the functional layers are composed of a chemical filtration functional layer 120 and a protective functional layer 130 , and the chemical filtration functional layer 120 and the protective functional layer 130 overlap front and back along the filtration direction.
[0140] The protective functional layer 130 has a porous structure and a pore size smaller than the particle size of the catalyst in the chemical filtration layer; the protective functional layer 130 is a PP fiber felt with a pore size of 90 μm and a thickness of 3 mm.
[0141] The chemical filtration functional layer 120 is a chemical filtration layer for filtering at least one volatile organic compound; the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; the thickness of the chemical filtration layer is 3 mm, and the air permeability is 3000 m 3 / m 2 ·h.
[0142] The chemical filtration functional layer 120 is connected to the protective functional layer 130 through a connecting layer, and the connecting layer is an ultrasonic composite layer. The ultrasonic composite layers are arranged in two locations symmetrically with respect to the center line of the filter material. Each ultrasonic composite layer 410 is composed of two parallel ultrasonic composite lines 411 with a spacing of 3 cm, and the ultrasonic composite line 411 is composed of composite nodes 412 with a length of 3 mm and a width of 1 mm arranged at a spacing of 2 mm.
[0143] Example 2
[0144] like Figure 2 As shown, the filter material of this embodiment has different functional layers, and all the functional layers are composed of a physical filtration functional layer and a chemical filtration functional layer 120 , and the physical filtration functional layer and the chemical filtration functional layer 120 overlap front and back along the filtration direction.
[0145] The chemical filtration functional layer 120 is a chemical filtration layer for filtering at least one volatile organic compound; the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; the thickness of the chemical filtration layer is 2 mm, and the air permeability is 4560 m 3 / m 2 ·h.
[0146] The physical filtration functional layer is a first physical filtration layer for filtering solid particles in the filtered object; the first physical filtration layer is a metal filtration layer 111, and the thickness of the metal filtration layer 111 is 1.5 mm and the pore size is 80 μm.
[0147] The physical filtration functional layer and the chemical filtration functional layer 120 are connected by a connecting layer, and the connecting layer is an ultrasonic composite layer. The ultrasonic composite layers are three and are symmetrically arranged with the center line of the filter material. The ultrasonic composite layers 410 on both sides are composed of multiple ultrasonic composite lines 411 crossing each other, and the ultrasonic composite layer 410 in the middle is composed of one ultrasonic composite line 411, and the ultrasonic composite line 411 is composed of composite nodes 412 with a length of 3 mm and a width of 1 mm arranged at a spacing of 2 mm.
[0148] Example 3
[0149] like Figure 3 As shown, the filter material of this embodiment has different functional layers, and all the functional layers are composed of a physical filtration functional layer and a chemical filtration functional layer 120 , and the physical filtration functional layer and the chemical filtration functional layer 120 overlap front and back along the filtration direction.
[0150] The chemical filtration functional layer 120 is a chemical filtration layer for filtering at least one volatile organic compound; the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; the thickness of the chemical filtration layer is 1 mm, and the air permeability is 5720 m 3 / m 2 ·h.
[0151] The physical filtration functional layer is composed of a first physical filtration layer for filtering solid particles in the filtered object and a second physical filtration layer 113 for filtering at least one volatile organic compound, and the first physical filtration layer and the second physical filtration layer 113 overlap front and back along the filtering direction. The first physical filtration layer is a fiber filtration layer 112, and the fiber filtration layer 112 is composed of ultra-fine PP fibers and has a thickness of 3 mm. The second physical filtration layer 113 includes activated carbon, and the particle size of the activated carbon is 0.01 to 0.1 mm.
[0152] The physical filtration functional layer and the chemical filtration functional layer 120 are connected by a connecting layer disposed between the first physical filtration layer and the chemical filtration layer. The connecting layer is a rubber thread layer 510 with a thickness of 0.5 mm. The second physical filtration layer 113 is filled in the gap with a thickness of 0.5 mm formed by the rubber thread layer 510 between the first physical filtration layer and the chemical filtration layer. The rubber thread layer 510 is composed of rubber threads 512 with a diameter of 0.05 mm. There are four rubber thread layers 510 in total and they are respectively disposed at the edge of the contact surface between the first physical filtration layer and the chemical filtration layer to fill as much activated carbon powder as possible. The width of each rubber thread layer 510 is 5 cm. Figure 4 As shown, each rubber wire layer 510 includes multiple layers of rubber wire units 511 from top to bottom, the deposition directions of two adjacent layers of rubber wire units 511 are different, and each layer of rubber wire units 511 includes multiple rubber wires 512 arranged at a spacing of 5 mm.
[0153] The preparation method of the filter material comprises the following steps:
[0154] (1) Use Figure 5 The mold shown is placed on the surface of the chemical filtration functional layer 120, and then activated carbon is sprinkled into the through holes of the mold, and the second physical filtration layer 113 is formed after flattening and compacting;
[0155] (2) Remove the mold, spray hot melt adhesive on the surface of the chemical filtration functional layer 120 where no activated carbon is sprinkled, and then bond the first physical filtration layer to the chemical filtration functional layer 120 to obtain the filtration material.
[0156] Example 4
[0157] like Figure 6 As shown, the filter material of this embodiment has different functional layers, and all functional layers are composed of a physical filtration functional layer, a chemical filtration functional layer 120 and a protective functional layer 130, and the physical filtration functional layer, the chemical filtration functional layer 120 and the protective functional layer 130 overlap front and back along the filtration direction.
[0158] The protective functional layer 130 has a porous structure and a pore size smaller than the particle size of the catalyst in the chemical filtration layer; the protective functional layer 130 is electrostatic cotton with a pore size of 90 μm and a thickness of 1 mm.
[0159] The chemical filtration functional layer 120 is a chemical filtration layer for filtering at least one volatile organic compound; the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; the thickness of the chemical filtration layer is 0.5 mm, and the air permeability is 6830 m 3 / m 2 ·h.
[0160] The physical filtration functional layer is composed of a first physical filtration layer for filtering solid particles in the object to be filtered. The first physical filtration layer is composed of a metal filtration layer 111 and a fiber filtration layer 112 which are overlapped front and back along the filtration direction. The metal filtration layer 111 has a thickness of 0.8 mm and a pore size of 60 μm. The fiber filtration layer 112 is composed of ultrafine PP fibers and has a thickness of 0.8 mm.
[0161] An ultrasonic composite layer 410 is provided between the protective functional layer 130 and the chemical filtration functional layer 120. The setting parameters of the ultrasonic composite layer 410 are the same as those of Example 1 or Example 2. A rubber wire layer 510 is provided between the chemical filtration functional layer 120 and the fiber filtration layer 112 and between the fiber filtration layer 112 and the metal filtration layer 111. There are two rubber wire layers 510 in each interface and they are symmetrically arranged with respect to the center line of the filter material. Each rubber wire layer 510 has a thickness of 50 μm and a width of 6 cm. The rubber wire layer 510 is composed of rubber wires 512 with a diameter of 0.05 mm. Figure 4 As shown, each rubber wire layer 510 includes multiple layers of rubber wire units 511 from top to bottom, the deposition directions of two adjacent layers of rubber wire units 511 are different, and each layer of rubber wire units 511 includes multiple rubber wires 512 arranged at a spacing of 10 mm.
[0162] Example 5
[0163] like Figure 7 As shown, the filter material of this embodiment has different functional layers, and all the functional layers are composed of a physical filter functional layer, a chemical filter functional layer 120 and a protective functional layer 130 which overlap front and back along the filtering direction.
[0164] The chemical filtration functional layer 120 is a chemical filtration layer for filtering at least one volatile organic compound; the chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support and a formaldehyde decomposition catalyst attached to the breathable support; the thickness of the chemical filtration layer is 0.1 mm, and the air permeability is 8000 m 3 / m 2 ·h.
[0165] The physical filtration functional layer is composed of a first physical filtration layer for filtering solid particles in the filtered material and a second physical filtration layer 113 for filtering at least one volatile organic compound, and the first physical filtration layer and the second physical filtration layer 113 overlap front and back along the filtering direction. The first physical filtration layer is composed of a metal filtration layer 111 and a fiber filtration layer 112 overlapping front and back along the filtering direction, the metal filtration layer 111 is 0.12 mm thick and has a pore size of 40 μm, and the fiber filtration layer 112 is composed of ultra-fine PP fibers and has a thickness of 0.18 mm. The second physical filtration layer 113 includes activated carbon, and the particle size of the activated carbon is 0.01 to 0.1 mm.
[0166] The protective functional layer 130 has a porous structure and a pore size smaller than the particle size of the catalyst in the chemical filtration layer; the protective functional layer 130 is a PET fiber felt with a pore size of 90 μm and a thickness of 0.1 mm.
[0167] An ultrasonic composite layer 410 is provided between the protective functional layer 130 and the chemical filtration functional layer 120, and the setting parameters of the ultrasonic composite layer 410 are the same as those of Example 1 or Example 2. A rubber layer 510 is provided between the fiber filtration layer 112 and the metal filtration layer 111, and the setting parameters of the rubber layer 510 are the same as those of Example 4. A rubber layer 510 is provided between the fiber filtration layer 112 and the chemical filtration functional layer 120, and the setting parameters of the rubber layer 510 are the same as those of Example 3.
[0168] The preparation method of the filter material comprises the following steps:
[0169] (1) The protective functional layer 130 and the chemical filtration functional layer 120 are compositely connected by ultrasonic wave;
[0170] (2) Use Figure 5 The mold shown is placed on the surface of the chemical filtration functional layer 120, and then activated carbon is sprinkled into the through holes of the mold, and the second physical filtration layer 113 is formed after flattening and compacting;
[0171] (3) Remove the mold, spray hot melt adhesive on the surface of the chemical filtration functional layer 120 where no activated carbon is sprinkled, and then bond the fiber filtration layer 112 to the chemical filtration functional layer 120.
[0172] (4) The fiber filter layer 112 and the metal filter layer 111 are connected by spraying glue to obtain the filter material.
[0173] Example 6
[0174] Compared with Example 5, the filter material of this embodiment has the following differences: Figure 8As shown, a lap strip is provided between the fiber filter layer 112 and the chemical filter functional layer 120, and the upper and lower surfaces of the lap strip are respectively connected to the fiber filter layer 112 and the chemical filter functional layer 120 through ultrasonic compounding.
[0175] The preparation method of the filter material comprises the following steps:
[0176] (1) The protective functional layer 130 and the chemical filtration functional layer 120 are compositely connected by ultrasonic wave;
[0177] (2) Ultrasonic composite connection is used around the chemical filtration functional layer 120 to form a space for placing activated carbon. The activated carbon is then spread in the space and scraped and compacted to form a second physical filtration layer 113.
[0178] (3) The fiber filter layer 112 is then bonded to the overlap strip by ultrasonic composite bonding.
[0179] (4) The fiber filter layer 112 and the metal filter layer 111 are connected by spraying glue to obtain the filter material.
[0180] Comparative Example 1 (Comparative Example of Example 1)
[0181] Compared with Example 1, the filter material of this embodiment has the following differences: Fig. 9 As shown, uniformly distributed ultrasonic composite lines 411 are provided on the entire contact surface between the chemical filtration functional layer 120 and the protective functional layer 130 .
[0182] Comparative Example 2 (Comparative Example of Example 1)
[0183] Compared with Example 1, the filter material of this embodiment has the following differences: Fig.10 As shown, a uniformly distributed rubber thread layer 510 is provided on the entire contact surface between the chemical filtration functional layer 120 and the protective functional layer 130. The rubber thread layer 510 is composed of two layers of rubber thread units 511, upper and lower. Each layer of rubber thread units 511 is composed of rubber threads 512 arranged at a spacing of 10 mm, and the diameter of the rubber thread 512 is 0.05 mm.
[0184] It is verified that compared with control examples 1-2, embodiment 1 has higher air permeability.
[0185] In a filter assembly using the filter material 100 of any one of embodiments 1-6, the filter material 100 is used as the filter portion 210 and can be used folded or unfolded. Figure 11-12 As shown, the folded filter material 100 has a pleated structure 101, one pair of opposite sides of the filter material 100 is a pleated wave side 101a, and the other pair of opposite sides is a straight side 101b. At this time, the structure of the filter assembly is as shown in FIG. Figure 13-14 As shown, it includes a filter portion 210, a positioning portion 220 and a sealing portion 230, which are specifically as follows:
[0186] The positioning part 220 includes a positioning frame 221 arranged around the filter material 100 so as to confine the filter material 100 therein and open both sides of the filter material 100 to the outside, a conductive component 223 for conductively connecting with the metal filter layer in the filter material 100, and a pleated conformal component 222 arranged on the side of the filter material 100. The pleated conformal component 222 includes a support arranged between a plurality of pairs of adjacent pleated waves 101c of the filter material 100 at intervals, and the support is composed of positioning glue 222a respectively filled between the plurality of pairs of adjacent pleated waves 101c and solidified, and the positioning glue 222a is only filled between the peaks of the corresponding adjacent pleated waves 101c and the filling depth is 0.8 cm. The conductive component 223 includes a contact 223a arranged on the positioning part 220 (the contact position can be located on the side of the positioning frame 221, and when the filter assembly 200 is installed on a parent device such as a filter, the side of the contact 223a just contacts with the electrical connection terminal on the parent device such as the filter) and a copper ear 223b arranged on the positioning part 220 for connecting with the metal filter layer. The positioning frame 221 is a rectangular positioning frame matching the filter material 100, and the positioning frame 221 includes: a side positioning frame 221a, wherein a sealing material is arranged between the side positioning frame 221a and the filter material 100; an upper positioning frame 221b, wherein the upper positioning frame 221b is arranged at the upper end of the side positioning frame 221a and extends along the top edge of the side positioning frame 221a; and a lower positioning frame 221c, wherein the lower positioning frame 221c is arranged at the lower end of the side positioning frame 221a and extends along the bottom edge of the side positioning frame 221a. The upper positioning frame 221b is separately connected to the side positioning frame 221a, and the bottom surface of the upper positioning frame 221b has a step surface 221b1 for adapting to the upper end of the side positioning frame 221a, and the sealant between the upper positioning frame 221b and the side positioning frame 221a basically covers the two parallel planes on the step surface 221b1.
[0187] The sealing part 230 includes a sealing material arranged between the filter material 100 and the positioning part 220 to prevent the filtered material from penetrating the inner boundary area of the positioning frame without passing through the filter material 100. The sealing material includes a sealant bonded between the straight edge 101b of the filter material 100 and the positioning frame 221, and a sealing plate 231 located between the pleated wave-shaped edge 101a of the filter material 100 and the positioning frame 221. The surface of the filter material 100 where the straight edge 101b is located is directly bonded to the corresponding inner side surface of the positioning frame 221 through the sealant. The inner side surface of the sealing plate 231 is bonded to the surface where the pleated wave-shaped edge 101a of the corresponding filter material 100 is located through the sealant, and the outer side surface is bonded to the corresponding inner side surface of the positioning frame 221 through the sealant.
[0188] A filter using the filter material 100 of one of Examples 1-6 is as follows: Fig.15 As shown, it includes an air inlet 310, an air outlet 320 and an air duct between the air inlet 310 and the air outlet 320, and the above-mentioned filter assembly 200 is installed on the air duct, and the windward side of the filter assembly 200 is connected to the air inlet 310, and the windward side is connected to the air outlet 320. Due to the special structure of the filter material 100, the thickness of the filter assembly 200 is relatively thin, and the filter assembly 200 can be directly installed in an existing household air conditioner. In addition, when the filter 300 is in operation, the metal filter layer of the filter assembly 200 can be selectively charged or uncharged.
[0189] In the following embodiments, the embodiments of the formaldehyde decomposition catalyst are represented by "Example A1", "Example A2", "Example A3", etc. (and so on). The embodiments of the formaldehyde decomposition catalytic felt are represented by "Example B1", "Example B2", "Example B3", etc. (and so on).
[0190] Example A1
[0191] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 95 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 70 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 4:3, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 50 L, then the volume of the manganese sulfate solution in the second titration tank is calculated according to the above conditions and the result. The molecular weight of potassium permanganate and manganese sulfate is calculated to be approximately equal to 50L; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the bottom water of 100L pre-stored in the mixing reactor, and the titration time is set to 10min (that is, the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are all added dropwise within a time period of 10min), and then the mixed solution is fully stirred at 80°C for 2h; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain a formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0192] Fig.16 is a scanning electron microscope image of the formaldehyde decomposition catalyst of Example A1, Fig.16 Figures (a)-(d) are photographs of the field of view selected on the slide without tendency during microscopic observation. Fig.17 for Fig.16 X-ray diffraction (XRD) pattern of the formaldehyde decomposition catalyst shown.
[0193] according to Fig.16 As shown, the formaldehyde decomposition catalyst of Example A1 is mainly composed of submicron-micron petal-shaped particles, wherein the diameter (i.e., particle size) of the micron-sized petal-shaped particles is mainly distributed between 1 and 3 μm, and the diameter of the submicron-sized petal-shaped particles is mainly distributed between 0.1 and 1 μm.
[0194] Further observation reveals that these submicron-micron petal-shaped particles are often in a state of agglomeration, and due to the uneven distribution of particle diameters, a large number of submicron petal-shaped particles are irregularly distributed around the micron petal-shaped particles, which increases the specific surface area of the submicron-micron petal-shaped particles after agglomeration.
[0195] according to Fig.17 As shown, combined with the standard diffraction peaks of (001), (002) and (111) crystal planes of δ-crystalline manganese dioxide (JCPDS 80-1089), and through the literature "Study on Controllable Preparation Conditions of Manganese Dioxide with Different Crystalline Forms, Wang Ge et al., Inorganic Salt Industry, August 2017", it can be confirmed that the submicron-micron petal-shaped particles of the formaldehyde decomposition catalyst of Example A1 are δ-crystalline MnO2.
[0196] Example A2
[0197] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 60 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 70 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 1, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 50 L, and the volume of the manganese sulfate solution in the second titration tank is calculated according to the above conditions and combined with the molecular weights of potassium permanganate and manganese sulfate; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the bottom water of a volume of 100 L pre-stored in a mixing reactor, the titration time is set to 10 min, and then the mixed solution is fully stirred at 80° C. for 2 hours; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain the formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0198] Scanning electron microscopy observation of the formaldehyde decomposition catalyst of Example A2 determined that the formaldehyde decomposition catalyst of Example A2 met the characteristics of being mainly composed of submicron-micron petal-shaped particles, and the specific diameter distribution of its submicron-micron petal-shaped particles was similar to that of the formaldehyde decomposition catalyst of Example A1.
[0199] The X-ray diffraction test conducted on the formaldehyde decomposition catalyst of Example A2 determined that the submicron-micron petal-shaped particles of the formaldehyde decomposition catalyst of Example A2 were delta-crystalline MnO2.
[0200] Example A3
[0201] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 110 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 120 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 1.1, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 50 L, and the volume of the manganese sulfate solution in the second titration tank is calculated according to the above conditions and combined with the molecular weights of potassium permanganate and manganese sulfate; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the bottom water of a volume of 100 L pre-stored in a mixing reactor, the titration time is set to 10 min, and then the mixed solution is fully stirred at 80° C. for 2 hours; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain the formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0202] Scanning electron microscopy observation of the formaldehyde decomposition catalyst of Example A3 determined that the formaldehyde decomposition catalyst of Example A3 met the characteristics of being mainly composed of submicron-micron petal-shaped particles, and the specific diameter distribution of its submicron-micron petal-shaped particles was similar to that of the formaldehyde decomposition catalyst of Example A1.
[0203] The formaldehyde decomposition catalyst of Example A3 was subjected to an X-ray diffraction test to determine that the submicron-micron petal-shaped particles of the formaldehyde decomposition catalyst of Example A2 were δ-crystalline MnO2.
[0204] Example A4
[0205] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 95 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 70 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 4:3, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 100 L, then the volume of the manganese sulfate solution in the second titration tank is calculated according to the above conditions and in combination with the molecular weights of potassium permanganate and manganese sulfate to be approximately equal to 100 L; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the bottom water of a volume of 200 L pre-stored in a mixing reactor, the titration time is set to 18 min, and then the mixed solution is fully stirred at 80° C. for 2 h; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain the formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0206] Scanning electron microscopy observation of the formaldehyde decomposition catalyst of Example A4 determined that the formaldehyde decomposition catalyst of Example A4 met the characteristics of being mainly composed of submicron-micron petal-shaped particles, and the unevenness of the diameter distribution of its submicron-micron petal-shaped particles was greater than that of the formaldehyde decomposition catalyst of Example A1.
[0207] The formaldehyde decomposition catalyst of Example A4 was subjected to an X-ray diffraction test to determine that the submicron-micron petal-shaped particles of the formaldehyde decomposition catalyst of Example A2 were δ-crystalline MnO2.
[0208] Example A5
[0209] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 95 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 70 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 4:3, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 300 L, then the volume of the manganese sulfate solution in the second titration tank is calculated according to the above conditions and in combination with the molecular weights of potassium permanganate and manganese sulfate to be approximately equal to 300 L; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the bottom water of a volume of 600 L pre-stored in the mixing reactor, the titration time is set to 35 min, and then the mixed solution is fully stirred at 80° C. for 2 h; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain the formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0210] Fig.18 is a scanning electron microscope image of the formaldehyde decomposition catalyst of Example A5, Fig.18 Figures (a)-(d) are photographs of the field of view selected on the slide without tendency during microscopic observation. Fig.18 As shown, the formaldehyde decomposition catalyst of Example A5 is mainly composed of submicron-micron petal-shaped particles, wherein the diameter of the micron-sized petal-shaped particles is mainly distributed between 1 and 4 μm, and the diameter of the submicron-sized petal-shaped particles is mainly distributed between 0.3 and 1 μm.
[0211] Further observation shows that these submicron-micron petal-shaped particles are often in a state of aggregation, and due to the uneven distribution of particle diameters, a large number of submicron-micron petal-shaped particles are irregularly distributed around the micron-sized petal-shaped particles (this phenomenon is more obvious than the formaldehyde decomposition catalyst of Example A1), so that the specific surface area of the submicron-micron-sized petal-shaped particles after aggregation is larger. The X-ray diffraction test on the formaldehyde decomposition catalyst of Example A5 determined that the submicron-micron-sized petal-shaped particles of the formaldehyde decomposition catalyst of Example A5 are δ-crystalline MnO2.
[0212] It is speculated that the uneven distribution of δ-crystalline MnO2 particle diameter is related to the volume of the raw potassium permanganate solution or manganese sulfate solution and the corresponding titration time. It is further speculated that when the volume of the raw potassium permanganate solution or manganese sulfate solution is large and the corresponding titration time is long, the grains that nucleate first will mainly grow.
[0213] Example A6
[0214] Potassium permanganate, manganese sulfate and water are used as raw materials for mixed reaction to obtain a formaldehyde decomposition catalyst, specifically: potassium permanganate is configured into a potassium permanganate solution with a concentration of 95 g / L and placed in a first titration tank, manganese sulfate is configured into a manganese sulfate solution with a concentration of 70 g / L and placed in a second titration tank, the amount of substance ratio between the potassium permanganate in the first titration tank and the manganese sulfate in the second titration tank is 4:3, the volume of the potassium permanganate solution in the first titration tank is set as the reference volume, the reference volume is set to 50 L, and the manganese sulfate solution in the second titration tank is 4:3. The liquid volume is calculated to be approximately equal to 50L based on the above conditions and the molecular weights of potassium permanganate and manganese sulfate; then the potassium permanganate solution in the first titration tank and the manganese sulfate solution in the second titration tank are respectively added dropwise to the 100L bottom water pre-stored in the mixing reactor, the titration time is set to 10min, and then the mixed solution is fully stirred at 80°C for 2h; thereafter, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain a formaldehyde decomposition catalyst; finally, the mixed solution after the reaction is completed is centrifuged and dehydrated to obtain a formaldehyde decomposition catalyst. The obtained formaldehyde decomposition catalyst is then alkali washed, cleaned, dried and dispersed.
[0215] The alkali washing refers to washing the formaldehyde decomposition catalyst with alkali solution. In this embodiment, the formaldehyde decomposition catalyst is added into deionized water, and then a certain amount of alkali solution is added to adjust the pH value of the solution to 9-11, and finally centrifugally dehydrated to obtain the formaldehyde decomposition catalyst.
[0216] Comparative Example 1
[0217] The formaldehyde decomposition catalyst is obtained by mixing potassium permanganate and anhydrous ethanol as raw materials. Specifically, potassium permanganate is prepared into a potassium permanganate solution with a concentration (mass percentage) of 1.25%, 4L of the potassium permanganate solution is mixed with 1L of anhydrous ethanol and stirred, and the mixture is reacted at room temperature for 10 hours. The formaldehyde decomposition catalyst is obtained by centrifugal dehydration from the mixed solution after the reaction is completed, and the obtained formaldehyde decomposition catalyst is then washed, dried and dispersed.
[0218] Fig.19 is a scanning electron microscope image of the formaldehyde decomposition catalyst of Comparative Example 1, Fig.19 Figures (a) and (b) are photographs of the field of view selected on the slide without tendency during microscopic observation. Fig.19 As shown, the formaldehyde decomposition catalyst of Comparative Example 1 is mainly composed of nano-sized particles agglomerated. The X-ray diffraction test conducted on the formaldehyde decomposition catalyst of Comparative Example 1 determined that the formaldehyde decomposition catalyst of Comparative Example 1 is δ-crystalline MnO2.
[0219] The formaldehyde decomposition catalysts of Example A1, Example A5, and Comparative Example 1 were used to test the formaldehyde removal performance. The test principle and method are as follows: a closed test chamber with a size of 550 mm×415 mm×315 mm was prepared, and a formaldehyde injection port and a formaldehyde concentration test instrument were provided. An air outlet and an air inlet were respectively provided on both sides of the test chamber. The air outlet and the air inlet were connected by a pipe with a diameter of 200 mm, and a fan was installed on the pipe. In addition, a set of flanges were installed on the pipe for loading and unloading the formaldehyde decomposition catalyst for testing.
[0220] Before the test, a certain amount of formaldehyde decomposition catalyst was evenly spread on a piece of PP breathable film, with a spreading amount of 0.04g / cm 2 Then, the formaldehyde decomposition catalyst is covered with another piece of PP breathable film, and then the two pieces of PP breathable films containing the formaldehyde decomposition catalyst are clamped between the flanges to fix the formaldehyde decomposition catalyst in the pipeline.
[0221] During the test, a certain volume and concentration of formaldehyde solution was heated and injected into the test chamber through the formaldehyde injection port, so that the initial formaldehyde concentration in the test chamber was 1.4-2.0 mg / m 3 When the formaldehyde concentration in the test chamber increases to the maximum value and stabilizes for 1 minute, start the fan and start timing. Record the formaldehyde concentration in the chamber every 5 minutes. The test duration is set to 15 minutes. During this period, the fan power remains constant (wind speed is about 3m / s). After 15 minutes, inject formaldehyde again in the above manner and repeat the 15-minute test. Each formaldehyde decomposition catalyst is tested 4 times.
[0222] The curves of the formaldehyde concentration in the experimental chamber changing with time obtained by using the formaldehyde decomposition catalysts of Example A1, Example A5 and Comparative Example 1 to perform the above formaldehyde removal performance test are respectively Fig. 20 , Fig.21 and Fig. 22 .
[0223] according to Fig. 20 , Fig.21 and Fig. 22 As shown, it can be calculated that the formaldehyde removal efficiency in the first 10 minutes of the formaldehyde removal performance test process using the formaldehyde decomposition catalyst of Example A1 is 76.2%, the formaldehyde removal efficiency in the first 10 minutes of the formaldehyde removal performance test process using the formaldehyde decomposition catalyst of Example A5 is 81.2%, and the formaldehyde removal efficiency in the first 10 minutes of the formaldehyde removal performance test process using the formaldehyde decomposition catalyst of Comparative Example 1 is 64%.
[0224] The formaldehyde removal efficiency of the formaldehyde decomposition catalysts of Examples A1 and A5 is better than that of the formaldehyde decomposition catalyst of Comparative Example 1. The possible reason is presumably that: although the formaldehyde decomposition catalysts of the comparative example are composed of nano-scale particles, they are easy to agglomerate, especially when attached to a breathable support, these fine particles aggregate into blocks, which is not conducive to sufficient contact with formaldehyde in the air; while the formaldehyde decomposition catalysts of the embodiments have uneven particle diameter distribution, and a large number of submicron petal-shaped particles are irregularly distributed around the micron-sized petal-shaped particles, so that the submicron-micron-sized petal-shaped particles are agglomerated, which is conducive to sufficient contact with formaldehyde in the air.
[0225] In addition, olfactory tests by multiple testers (the test samples were placed 15 cm below the testers' noses) showed that the formaldehyde decomposition catalyst of Example A6 had significantly lower odor than the formaldehyde decomposition catalysts of Examples A1-A5.
[0226] The formaldehyde decomposition catalyst involved in the inventions and creations involved in this application specification can be directly used as a product to implement the manufacturing, sales and use of the product, or it can be applied to formaldehyde catalytic decomposition felt to implement the manufacturing, sales and use of the formaldehyde catalytic decomposition felt. Fig.23 This is a scanning electron microscope image of a formaldehyde decomposition catalytic felt in the invention involved in this application specification. Fig.23 As shown, the formaldehyde decomposition catalytic felt involved in the invention involved in the present application specification includes a breathable support 121a and a formaldehyde decomposition catalyst (belonging to the decomposition catalyst 121b) attached to the breathable support.
[0227] like Fig.23As shown, the formaldehyde decomposition catalyst is distributed on the outside of the material constituting the breathable support 121a and is mainly filled in the pores between the materials constituting the breathable support.
[0228] In addition, the formaldehyde decomposition catalyst generally further includes an adhesive distributed on the formaldehyde decomposition catalyst so that it can be more firmly attached to the breathable support 121a. The adhesive is preferably an acrylic adhesive or a polyurethane adhesive, which will not adversely affect the performance of the formaldehyde decomposition catalyst.
[0229] If the weight of the formaldehyde decomposition catalyst is divided by the area of the windward surface of the air-permeable support 121a, the relative attachment amount of the formaldehyde decomposition catalyst on the air-permeable support 121a is set, based on the formaldehyde removal efficiency of the formaldehyde decomposition catalyst of the invention involved in the specification of this application, the relative attachment amount is generally 40 g / m 2 As a result, the formaldehyde decomposition catalytic felt basically has a commercially acceptable formaldehyde removal effect.
[0230] Since the formaldehyde decomposition catalyst is attached to the air permeable support 121a, especially when the relative attachment amount is 40 g / m 2 When the pressure difference is above 100Pa, the air permeability of the air permeable support 121a will be significantly reduced. In order to make the formaldehyde decomposition catalytic felt have both good formaldehyde removal effect and reasonable air permeability, it is recommended that the air permeability of the air permeability of the air permeable support 121a be ≥3000m at a pressure difference of 100Pa. 3 / m 2 ·h breathable fiber felt.
[0231] Since the filter material related to the invention involved in this application specification includes different functional layers, and the formaldehyde decomposition catalytic felt is only one of the functional layers, in order to ensure the air permeability of the entire filter material, the air permeability of the air permeability support 121a is preferably ≥5500m at a pressure difference of 100Pa. 3 / m 2 ·h breathable fiber felt.
[0232] The above “air permeability at 100Pa pressure difference” can be expressed in terms of its unit “m 3 / m 2 ·h" is understood. Specifically, "air permeability at 100Pa pressure difference" refers to the value of cubic meters of air passing through the formaldehyde decomposition catalytic felt per unit square meter per hour under a pressure difference of 100Pa.
[0233] Breathable fiber felts meeting the above air permeability requirements can be obtained from the prior art, such as PP fiber felts, PET fiber felts, etc. PP fiber felts and PET fiber felts not only have good air permeability, but also have suitable properties such as strength.
[0234] The formaldehyde catalytic decomposition felt in the invention involved in this application specification can not only be used as one of the functional layers of the filter material, but also has other application methods. At this time, the shape, performance and other aspects of the breathable support 121a in the formaldehyde catalytic decomposition felt can also be greatly changed.
[0235] In an occasion with a high formaldehyde concentration (such as a furniture factory, a paint factory, etc.), in order to better remove formaldehyde, a foam-like porous support body can be used as the air-permeable support 121a in the formaldehyde catalytic decomposition felt so as to attach more formaldehyde decomposition catalysts. In order to independently install the formaldehyde catalytic decomposition felt on a specific channel, the air-permeable support 121a can be a support net, and the support net can be a woven net, a perforated net, a diagonal net, etc.
[0236] Example B1
[0237] The formaldehyde decomposition catalyst of Example A1 is mixed with a dispersant and an adhesive to form a slurry, wherein the adhesive is acrylic acid and the dispersant is water. The breathable support 121a adopts PP fiber felt. The slurry is attached to the PP fiber felt by a slurry drawing process. During slurry drawing, the strip composed of PP fiber felt is immersed in the slurry under the drive of the conveyor roller, and then rises vertically from the surface of the slurry, and then passes through the channel formed between a pair of scrapers located above the slurry. Each of the scrapers in the pair of scrapers moves parallel to the corresponding PP fiber felt surface, thereby applying an extrusion force perpendicular to the surface of the PP fiber felt to the formaldehyde decomposition catalyst, thereby squeezing and dispersing the formaldehyde decomposition catalyst attached to the PP fiber felt in the pores between the materials constituting the breathable support, and finally the formaldehyde catalytic decomposition felt is dried to obtain the formaldehyde catalytic decomposition felt. After drying, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt is about 40g / m 2 .
[0238] Example B2
[0239] On the basis of Example B1, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was increased. After drying, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was about 60 g / m 2 .
[0240] Example B3
[0241] On the basis of Example B1, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was increased. After drying, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was about 80 g / m 2 .
[0242] Example B4
[0243] On the basis of Example B1, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was increased. After drying, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was about 100 g / m 2 .
[0244] Example B5
[0245] On the basis of Example B1, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was increased. After drying, the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt was about 120 g / m 2 .
[0246] Example B6
[0247] On the basis of Example B2, an extrusion process is added between the pulping process and the drying step. The extrusion process includes a pair of pressing rollers, a channel is formed between the pair of pressing rollers, and each of the pair of pressing rollers rolls parallel to the surface of the corresponding formaldehyde catalytic decomposition felt, thereby further squeezing and dispersing the formaldehyde decomposition catalyst attached to the PP fiber felt into the pores between the materials constituting the breathable support.
[0248] The formaldehyde catalytic decomposition felt of Examples B1-B5 were used to test the formaldehyde removal performance. The test principle and method are basically the same as the principle and method of testing the formaldehyde removal performance of the formaldehyde decomposition catalyst. The difference is that the formaldehyde catalytic decomposition felt is directly clamped between the flanges without using a PP breathable film.
[0249] Fig.24 This is a test chart of the comprehensive performance of the formaldehyde catalytic decomposition felt of Examples B1-B5. Fig.24 In the figure, the horizontal axis is the relative attachment amount of the formaldehyde decomposition catalyst on the PP fiber felt, where "40" means the attachment amount is about 40g / m 2 , corresponding to the formaldehyde catalytic decomposition felt in Example B1, and the rest are similar. Fig.24 The left ordinate is the air volume, in m 3 / m 2 ·h, meaning the cubic meter of air passing through the formaldehyde decomposition catalytic felt per unit square meter per hour. The larger the value, the better the air permeability of the formaldehyde catalytic decomposition felt, and vice versa. Fig.24 The left ordinate is the formaldehyde removal rate, which can be calculated based on Figure 20-22 The displayed data is calculated based on the same data.
[0250] like Fig.24 As shown, the formaldehyde removal efficiency of the formaldehyde catalytic decomposition felt of Examples B1-B5 in the first 10 minutes of the formaldehyde removal performance test gradually increased from about 66% to 72%. Although there was a certain increase, the increase was not large.
[0251] The formaldehyde catalytic decomposition felts of Examples B1-B5 were used to perform air permeability tests, i.e., the cubic meter value of air passing through the formaldehyde decomposition catalytic felt per unit square meter per hour under a certain pressure difference (specifically 10 Pa). Due to the flow meter reading limit, when the formaldehyde catalytic decomposition felts of Examples B1-B5 were used to perform air permeability tests, six identical formaldehyde catalytic decomposition felts were stacked together for testing, so that the flow rate could be reduced to meet the flow meter reading limit.
[0252] like Fig.24 As shown, the air permeability of the formaldehyde catalytic decomposition felts of Examples B1-B5 decreases in sequence. When the relative attachment amount is 70 g / m 2 About (60g / m 2 ~70g / m 2 When the air permeability and formaldehyde removal efficiency of formaldehyde catalytic decomposition felt are optimal.
[0253] Although Fig.24 It is shown in the figure that when the relative adhesion is 120g / m 2 The air permeability of the formaldehyde catalytic decomposition felt is 0, but this phenomenon does not mean that the formaldehyde catalytic decomposition felt is not air permeable. This is because 6 pieces of the same formaldehyde catalytic decomposition felt are stacked together during the test, and in fact each piece of formaldehyde catalytic decomposition felt has a certain air permeability.
[0254] Fig.25 This is a comparison chart of the distribution uniformity of the formaldehyde decomposition catalyst of the formaldehyde catalytic decomposition felt of Example B2 and Example B6. This comparison chart is obtained by placing the two formaldehyde catalytic decomposition felts together for light observation. Through observation, it can be clearly seen that the distribution of the formaldehyde decomposition catalyst of the formaldehyde catalytic decomposition felt of Example B6 is significantly more uniform and delicate.
[0255] In the filter materials of Examples 1-6 and Comparative Examples 1-2, the formaldehyde decomposition catalyst and its preparation method adopt the formaldehyde decomposition catalyst and its preparation method provided in Example A1.
[0256] In the filter materials of Examples 1-6 and Comparative Examples 1-2, the formaldehyde decomposition catalytic felt used is the formaldehyde decomposition catalytic felt provided in Example B2.
[0257] The above is a description of the relevant contents of the present invention. A person skilled in the art will be able to implement the present invention based on these descriptions. Based on the above contents of the present invention, all other embodiments obtained by a person skilled in the art without creative work shall fall within the scope of protection of the present invention.
Claims
1. Filter material with different functional layers, characterized by: All the functional layers include a physical filtration functional layer, a chemical filtration functional layer (120) and a protective functional layer (130), wherein the physical filtration functional layer, the chemical filtration functional layer (120) and the protective functional layer (130) overlap front and back along the filtration direction; The chemical filtration functional layer (120) comprises a chemical filtration layer for filtering at least one volatile organic compound; The protective functional layer (130) has a porous structure and a pore size smaller than a particle size of the catalyst in the chemical filtration layer; The physical filtration functional layer comprises a first physical filtration layer for filtering solid particles in the filtered object and a second physical filtration layer (113) for filtering at least one volatile organic compound, wherein the first physical filtration layer and the second physical filtration layer (113) overlap front and back along the filtering direction; The first physical filter layer is composed of a metal filter layer (111) and a fiber filter layer (112) arranged front and back along the filtering direction; the fiber filter layer (112) has electrical insulation properties; The second physical filtration layer (113) includes activated carbon.
2. The filter material according to claim 1, characterized in that: The chemical filtration layer is a formaldehyde decomposition catalytic felt, which comprises a breathable support (121a) and a formaldehyde decomposition catalyst (121b) attached to the breathable support (121a).
3. The filter material according to claim 2, characterized in that: The formaldehyde decomposition catalyst (121b) is mainly composed of submicron-micron petal-shaped particles formed by delta-crystalline MnO2; the protective functional layer (130) is PP fiber felt, PET fiber felt or electrostatic cotton.
4. The filter material according to claim 1, characterized in that: The filter material further comprises a connecting layer for connecting two adjacent functional layers.
5. The filter material according to claim 4, characterized in that: The connecting layer is a rubber layer (510) and / or an ultrasonic composite layer (410).
6. The filter material according to claim 5, characterized in that: The rubber wire layer (510) comprises multiple layers of rubber wire units (511) distributed from top to bottom, and the deposition directions of two adjacent layers of rubber wire units (511) are different; the rubber wire units (511) are composed of rubber wires (512) with a diameter of ≤0.1 mm arranged at a certain interval.
7. The filter material according to claim 5, characterized in that: The ultrasonic composite layer (410) is composed of one or more ultrasonic composite lines (411), and the ultrasonic composite lines (411) are composed of composite nodes (412) with a length of ≤3 mm and a width of ≤1 mm arranged at a spacing of 1 to 3 mm.
8. The filter material according to claim 4, characterized in that: A symmetrically distributed connecting layer is only provided locally between two adjacent functional layers.
9. A filter assembly, characterized in that: The invention comprises a filter part using the filter material according to any one of claims 1 to 8.
